Effectiveness of Thinking Strategy on the basis of Creativity of Commerce StudentS - Gehlawat, Komal; Pandey, R. S. (JOURNAL OF INDIAN EDUCATION, 2024)
Creativity has emerged as the skill of the twenty-first century. Companies are looking for diversity not only in gender, age, ethnicity but also in thoughts and perception to spur innovation. Countries across the globe are recognising creativity as the core ability that needs to be developed among students. The National Education Policy (NEP 2020) aims to develop the creative and analytical skills of students through experimental learning. The present study aims to study the effect of thinking strategy, i.e., Cognitive Research Trust (CoRT) strategy on the creativity of students studying in Grade XII at Government aided schools located in Gurugram and Faridabad. The study was experimental and opted for a non-equivalent control group design. The experimental group was given exercises in thinking based on the CoRT strategy while the control group continued with the conventional lecture method. The intervention was given for three months at the pace of one period per working day. One-way ANCOVA results revealed that the CoRT strategy had a significant effect on the creativity of students when compared with the traditional lecture method. Therefore, it can be inferred that the CoRT strategy can play a substantial role in the cognitive development of students.